Economía de Las Universidades Nacionales (1990-2010) - Ospino Edery, Juan José Manuel Ysaac (2013)
This research for university law review for period 1970-2010, the analysis fixed budget to state universities, discriminating that designed those locates in the city of Lima, and intended for provincial. If follows that the state is supported by subtracting the budgets of state university, Which have prioritized spending compared to current capital, the implementation of Canon law mining and public universities receiving and the amounts received in the last five years, and limitations on spending. As final point, a comparative analysis of budget allocations to the university system of Andean group of countries.